2015
DOI: 10.14302/issn.2476-1710.jdt-15-719
|View full text |Cite
|
Sign up to set email alerts
|

Basal Serum Cortisol Levels, Depression And Medial Temporal Lobe Atrophy In Patients With Mild Cognitive Impairment And Alzheimer’s Disease

Abstract: Objectives: Changes in serum cortisol levels have been reported in Alzheimer's disease (AD) and Mild Cognitive Impairment (MCI). Atrophy of Medial Temporal Lobes (MTLs) is common in both conditions. Glucocorticoids are known to be neurotoxic and have been believed to cause damage to memory mechanisms in the brains; whether the same is applicable to AD/MCI is not known. Also, they have long been hypothesized to cause atrophy of MTLs but the proof of the same is lacking. The present study was performed to deline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…A study by Dhikav et al, presented that the cortisol levels of patients with AD were higher and yet were within normal limits. 4 However, in our study, the serum levels of cortisol in patients with AD were not within the normal range. The serum levels of cortisol in patients with AD were significantly higher than those in the control group.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…A study by Dhikav et al, presented that the cortisol levels of patients with AD were higher and yet were within normal limits. 4 However, in our study, the serum levels of cortisol in patients with AD were not within the normal range. The serum levels of cortisol in patients with AD were significantly higher than those in the control group.…”
Section: Discussioncontrasting
confidence: 74%
“…The chronic increase in the concentrations of cortisol is found to be markedly associated with hypertension and cerebral atrophy. 3,4 Fewer studies have shown that chronic stress also has an impact on the levels of cytokines, including Interleukin-6 (IL-6) that represent the extent of neuroinflammation, which is a pathological hallmark of AD. 5 IL-6 is a multifunctional cytokine from the neuropoietin family of cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…[ 97–99 ] Cortisol rhythm disruptions in older individuals may reflect the progression of neurodegeneration; although, not all studies support this assumption. [ 100–103 ] An association between MCI and cortisol rhythm changes has been reported by several studies, [ 15,21,102–125 ] some of which compared MCI patients with control groups. [ 114,115,123,124 ] For example, a mild elevation of morning cortisol was observed in cerebrospinal fluids from patients with MCI compared to healthy, age‐matched individuals.…”
Section: Circadian Rhythm Changes In Healthy Aging and MCImentioning
confidence: 99%